Inhibition of γ-glutamyl transferase suppresses airway hyperresponsiveness and airway inflammation in a mouse model of steroid resistant asthma exacerbation - Zhang, Cancan; Xu, Huisha; Netto, Keilah G.; Sokulsky, Leon A.; Miao, Yiyan; Mo, Zhongyuan; Meng, Yan; Du, Yingying; Wu, Chengyong; Han, Liyou; Zhang, Lirong; Liu, Chi; et al. (Frontiers in Immunology, 2023)
Introduction Despite recent advances, there are limited treatments available for acute asthma exacerbations. Here, we investigated the therapeutic potential of GGsTop, a γ-glutamyl transferase inhibitor, on the disease with a murine model of asthma exacerbation. Methods GGsTop was administered to mice that received lipopolysaccharide (LPS) and ovalbumin (OVA) challenges. Airway hyperresponsiveness (AHR), lung histology, mucus hypersecretion, and collagen deposition were analyzed to evaluate the hallmark features of asthma exacerbation. The level of proinflammatory cytokines and glutathione were determined with/without GGsTop. The transcription profiles were also examined. Results GGsTop attenuates hallmark features of the disease with a murine model of LPS and OVA driven asthma exacerbation. Airway hyperresponsiveness (AHR), mucus hypersecretion, collagen deposition, and expression of inflammatory cytokines were dramatically inhibited by GGsTop treatment. Additionally, GGsTop restored the level of glutathione. Using RNA-sequencing and pathway analysis, we demonstrated that the activation of LPS/NFκB signaling pathway in airway was downregulated by GGsTop. Interestingly, further analysis revealed that GGsTop significantly inhibited not only IFNγ responses but also the expression of glucocorticoid-associated molecules, implicating that GGsTop profoundly attenuates inflammatory pathways. Conclusions Our study suggests that GGsTop is a viable treatment for asthma exacerbation by broadly inhibiting the activation of multiple inflammatory pathways.